Production Cooperative Development Strategies: Management, HR, Digitalization, and Partnerships - Hasyim, Nurhasmi; Budiawan, Shella; Piola, Marina Paramitha S.; Islaku, Nadia Pratiwi (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2026)
Production cooperatives in Indonesia through an examination of various empirical studies and relevant literature. The focus of the study is directed at cooperatives in the production sector such as handicrafts, food, and processing of agricultural products that represent the potential of a community-based economy. The research method uses a literature study approach by combining sources from scientific journals, research reports, and credible digital references. The results of the study show that production cooperatives face various obstacles, including weak institutional management, limited access to capital, low capacity of human resources, and the suboptimal use of digital technology in marketing and production. In addition, the low level of member participation in decision-making and supervision also affects the performance of cooperatives. On the other hand, cooperatives that are able to implement good organizational governance, innovate products and marketing, and build partnerships with the government, universities, and the private sector have proven to be more adaptive and competitive. Thus, the production cooperative development strategy needs to be directed at strengthening internal capacity, increasing innovation, and optimizing partnership networks to encourage business sustainability and improve member welfare